iGestSaúde: self-efficacy and quality of life in cancer patients, supported in the self-management of symptoms associated with chemotherapy - Lima, Lígia (2024)
Introduction: Chemotherapy treatment can cause a set of adverse symptoms, with negative implications for the cancer patient´s well-being and quality of life, which can be minimized with-nurse-led interventions focused on promoting the self-management of these symptoms. Objective: To assess the perception of self-efficacy and quality of life in cancer patients undergoing chemotherapy, supported in person and via telephone in the self-management of chemotherapy symptoms. Method: This was a descriptive-correlational and longitudinal study with 51 cancer patients, followed up at three time points during the first month of chemotherapy treatment. Results and discussion: The results indicate a good perception of self-efficacy and QoL throughout the first month of chemotherapy. Nausea and vomiting were the most harmful symptoms, especially in the first phase. The results also suggest that the guidelines for monitoring and self-management of symptoms given by nurses may have been positive for adaptation to chemotherapy.